Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan, dan Konservatisme Akuntansi Terhadap Nilai Perusahaan - Mohammad Sholihin; Fina Fitriyana (InFestasi, 2024)
This study aims to examine the effect of tax planning, deferred tax expense, and accounting conservatism on firm value. The research population is LQ45 companies listed on the Indonesia Stock Exchange (IDX). Determination of the sample using purposive sampling technique, obtained as many as 18 companies with 90 observation data. The analysis technique and hypothesis testing were carried out with panel data regression analysis through Eviews 9. The results of this study indicate that tax planning and deferred tax expense has no effect on firm value, while accounting conservatism have an effect on firm value. Simultaneously tax planning, deferred tax liabilities, and accounting conservatism affect firm value. Conservative accounting principles that have been applied in financial reports are considered as a positive signal by investors that management or agents have taken conservative steps to prevent exaggeration of com-pany assets and income. Positive signals from investors will be able to increase and increase the value of the company which is reflected in the share price on the capital market.